Perfil clínico e epidemiológico de pacientes com câncer de mama no Hospital Regional Público da Transamazônica de 2017 a 2022 - MARIA, Amanda de Assis (2024)
Breast carcinoma, among malignancies, is identified as the most recurrent, especially in women worldwide. The signs and symptoms of this cancer, diagnosis, risk factors and screening are important factors for the prognosis and progression of the disease. In this way, the need to draw up an epidemiological profile of the Xingu Region was seen to encourage prevention strategies, new studies and sharing with society on this topic. This study was carried out due to the harmful consequences of breast neoplasia, given its diagnostic and epidemiological importance. In this way, the clinical and epidemiological profile of breast cancer in the Xingu Region was determined, checking the risk groups, new cases diagnosed, the frequency and distribution of this region in the period from 2017 to 2022, considering that this study will provide an overview of the Clinical and Epidemiological Profile on Breast CA of patients treated at HRPT, being the first work related to research on this topic in this location. The objective of the present study was to identify the epidemiological profile of patients with breast CA in the Xingu Region who were treated at the Mastology outpatient clinic of the Public Regional Hospital of Transamazônica, Altamira/PA. This is an epidemiological study, retrospective with a cross-sectional design, with sampling collected from primary data (medical records). Analysis of the medical records showed that almost 62% of the patients were from Altamira and the majority lived in urban areas (81.72%), all of them female. Furthermore, the most prevalent carcinoma was Ductal with 74.19% and the age of the patients when they received the diagnosis was between 40 and 59 years old, corresponding to 58%. In view of the study of the results, it was found that mammographic screening should start at the age of 40 in women without risk factors, as 32.24% were diagnosed with BREAST AC between 40 and 49 years of age. Finally, there is a need to expand and create public policies and studies related to the topic so that women, especially, are diagnosed in the early stages of the disease and the dissemination of knowledge about screening to reduce the damage of this carcinoma and improve quality of life.